2017
DOI: 10.5194/cp-2017-33
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate variability in subarctic area for the last two millennia

Abstract: Abstract. To put in perspective the recent climate change, it is necessary to extend the instrumental climate records with proxy data from palaeoclimate archives. Arctic climate variability for the last two millennia has been investigated using statistical and signal analyses from three regionally averaged records from the North Atlantic, Siberia and Alaska based on many sort of proxy data archived in the Arctic 2k database. In the North Atlantic and Alaska areas, the major climatic trend is characterized by l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
2
0
0
Order By: Relevance
“…Here, we neither aimed to check for their further inconsistencies nor attempted to evaluate their veracity but calculated the mean temperature records for different proxy types. In keeping with the Milankovitch scale forcing, these records show varying but generally declining summer temperatures over the mid-and late-Holocene times until the first millennium BCE, after which the tree-ring and especially the diatom and chironomid data indicate a transient rise in temperatures, followed by a subsequent temperature decline toward the coolest centuries of all records, in accordance with the "Little Ice Age" climate as frequently recorded in several types of proxy evidence around the circumpolar Arctic sites (Kaufman et al, 2009;Nicolle et al, 2018;Helama et al, 2021). Clearly, different types of proxy data come with their own characteristics.…”
Section: Differing Signals Of Orbital Forcingsupporting
confidence: 77%
“…Here, we neither aimed to check for their further inconsistencies nor attempted to evaluate their veracity but calculated the mean temperature records for different proxy types. In keeping with the Milankovitch scale forcing, these records show varying but generally declining summer temperatures over the mid-and late-Holocene times until the first millennium BCE, after which the tree-ring and especially the diatom and chironomid data indicate a transient rise in temperatures, followed by a subsequent temperature decline toward the coolest centuries of all records, in accordance with the "Little Ice Age" climate as frequently recorded in several types of proxy evidence around the circumpolar Arctic sites (Kaufman et al, 2009;Nicolle et al, 2018;Helama et al, 2021). Clearly, different types of proxy data come with their own characteristics.…”
Section: Differing Signals Of Orbital Forcingsupporting
confidence: 77%
“…In agreement with findings of Nicolle et al (2017), our results demonstrate this orbital cooling trend is not necessarily observed in all sub-regions, although Nicolle et al (2017) even exhibit a warming with a mean temperature rise of +0.5 ± 0.1…”
supporting
confidence: 81%